Hubungan Pengetahuan Dan Riwayat Penyakit Keluarga Dengan Perilaku Pemeriksaan Payudara Sendiri (Sadari) Pada Mahasiswi Di Akademi Kebidanan Banua Bina Husada Banjarbaru Kalimantan Selatan Tahun 2016 - Eka Handayani; Fakultas Kesehatan Masyarakat UNISKA (HB PRESS, 2016)
Breasts are one of the important organs of women are closely related to the reproductive function and femininity (beauty). Breast disorders not only provide pain disorders as well as diseases in general, but will also have the effect of aesthetic and psychological quirks. Cases of breast cancer in developing countries has reached more than 580,000 cases annually and approximately 372,000 patients, or 46% of the number of such cases died of the disease. Data WHO (World Health Organization) show that 78% of breast cancer for women aged 50 years and older. Breast self-examination is often called the BSE is an effective way to detect as early as possible a lump in the breast. This study aims to mengetahuai Relations Knowledge and Behavior Disease History Family With Breast Self Examination (BSE) On Student In Midwifery Academy BANUA Bina Husada Banjarbaru South Kalimantan year 2016. This type of research is analytic with cross sectional study. Who is the subject of research that student who studied at the Academy of obstetrics Banua Bina Husada 2014. The population of amounting to 344 female students and 179 female students sample quantities with simple random sampling technique. The data were processed and analyzed by Spearman Rank test to test the hypothesis. Conduct research results of BSE at 196 Academy student obstetrics BANUA Bina Husada are 139 (70.9%) of respondents who do not perform breast self-examination and 57 (13.9%) of respondents who perform breast self-examination. There is a relationship between the variables of knowledge and family history with breast self-examination behavior in AKBID Banua Bina Husada Banjarbaru South Kalimantan.